Yellow Book Learning Management in Islamic Boarding Schools - Alwiyah, Tuti; Samsun, Rodi Hayani; Warisno, Andi; Andari, An An; Anshori, M Afif (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Learning the yellow book is a teaching and learning process between teachers and students that involves the use of religious books in Arabic letters written by salaf scholars, ancient scholars printed on yellow paper called polar al-turats, the contents of which are treasures of creativity for the development of Islamic civilization in ancient times. The learning methods used in Islamic boarding schools are stratified based on the abilities of the founders of the Islamic boarding schools, ranging from basic to intermediate to high-level religious knowledge, derived from tools science, monotheism science, fiqh science, tasawuf science, and so on. A qualitative approach and descriptive methods were used in the study of yellow book learning management at the Tri Bhakti At-taqwa Rama Puja Islamic Boarding School in East Lampung, beginning with planning, implementation, and evaluation. The study concluded that the students at Tri Bhakti Al-Ihklas Rama Puja Islamic Boarding School, East Lampung, were divided into four levels: (1) ibtida, (2) tsanawi, (3) aliyah, and (4) ma’had aly. The management of yellow book learning at Tri Bhakti At-taqwa Islamic Boarding School has a management plan for yellow book learning by creating a schedule in accordance with the applicable curriculum and handing over the learning material that will be given to the students to the teacher, so that the teacher can deliver learning according to their respective levels.